2017
DOI: 10.1136/bjophthalmol-2017-310316
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for diabetic retinopathy in China: a multi-hospital-based cross-sectional study

Abstract: PurposeTo determine the prevalence and risk factors for diabetic retinopathy (DR) and sight-threatening diabetic retinopathy (STDR) in a multi-hospital-based DR screening programme among patients with diabetes in China, the Lifeline Express Diabetic Retinopathy Screening Program.MethodsPatients with diabetes in eight hospitals across mainland China (both southern and northern) from January 2014 to July 2016 were recruited in this programme. All participants underwent a standardised interview and examinations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
113
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 25 publications
27
113
2
4
Order By: Relevance
“…Diabetic retinopathy (DR) is the leading cause of visual impairment and blindness in the working population around the world. In China, DR is responsible for vision loss in 12.6% of diabetic patients and tends to occur in patients much younger than those in Western countries [1,2]. As a severe stage of DR, proliferative diabetic retinopathy (PDR) poses the greatest threat to visual function due to neovascular formation and development [3].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic retinopathy (DR) is the leading cause of visual impairment and blindness in the working population around the world. In China, DR is responsible for vision loss in 12.6% of diabetic patients and tends to occur in patients much younger than those in Western countries [1,2]. As a severe stage of DR, proliferative diabetic retinopathy (PDR) poses the greatest threat to visual function due to neovascular formation and development [3].…”
Section: Introductionmentioning
confidence: 99%
“…There were 657,200 cases of diabetes mellitus reported in 2017 in Nepal [2]. Several epidemiological studies have reported a high prevalence of DR ranging from 11.9% to 43.1% [3]. There are multiple risk factors for the development and progression of diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Cr.) were studied in various literatures [3,8,9,[11][12][13][14][15][16]. There is 29 times higher risk to develop blindness due to diabetic retinopathy than non-diabetic of similar age and gender [4].…”
Section: Introductionmentioning
confidence: 99%
“…National and international studies that have been conducted to determine the prevalence of diabetic retinopathy have reported values that range from 15% in some studies to 36% in others [19][20][21][22][23]. Studies from Saudi Arabia's southern region reported a prevalence of 36.4%, which is much higher than the previously reported prevalence of Health Prim Car, 2018 doi: 10.15761/HPC.1000134 11.3% in the same region by Al-Khaldi, et al [24].…”
Section: Discussionmentioning
confidence: 89%